Bacterial community are more susceptible to nanoplastics than algae community in aquatic ecosystems dominated by submerged macrophytes - Hao, Beibei; Wu, Haoping; You, Yi; Liang, Ying; Huang, Lihua; Sun, Yan; Zhang, Siyi; He, Bin (Water research (Oxford), 2023)
•Unravel NPs effects on algae and bacteria in macrophytes-dominated ecosystem.•NPs reduced the diversity of planktonic/phyllopheric bacteria rather than algae.•Environmental variables significantly affected and explained bacterial composition.•NPs reduce algae-bacteria and planktonic-phyllospheric microbial associations.•Bacterial community may act as a protective barrier for algae in natural habitats. As a ubiquitous emerging pollutant, microplastics can interact with algal and bacterial communities in aquatic ecosystems. Currently, knowledge on how microplastics influence algae/bacteria is mostly limited to toxicity tests using either monocultures of algae/bacteria or specific algal–bacterial consortium. However, information on the effect of microplastics on algal and bacterial communities in natural habitats is not easily available. Here, we conducted a mesocosm experiment to test the effect of nanoplastics on algal and bacterial communities in aquatic ecosystems dominated by different submerged macrophytes. The community structure of algae and bacteria suspended in the water column (planktonic) and attached to the surface of submerged macrophytes (phyllospheric) were identified, respectively. Results showed that both planktonic and phyllospheric bacteria were more susceptible to nanoplastics, and these variations driven by decreased bacterial diversity and increased abundance of microplastic-degrading taxa, especially in aquatic systems dominated by V. natans. The community composition of both algae and bacteria were influenced to varying degrees by nanoplastics and/or plant types, but RDA results showed that only bacterial community composition was strongly correlated with environmental variables. Correlation network analysis showed that nanoplastics not only reduced the intensity of associations between planktonic algae and bacteria (average degree reduced from 4.88 to 3.24), but also reduced proportion of positive correlations (from 64% to 36%). Besides, nanoplastics also decreased the algal/bacterial connections between planktonic and phyllospheric habitats. Our study elucidates the potential interactions between nanoplastics and algal-bacterial community in natural aquatic ecosystems. These findings suggest that in aquatic ecosystems, bacterial community are more vulnerable to nanoplastics and may serve as a protective barrier for algae community. Further research is needed to reveal the protective mechanism of bacteria against algae at the community level. [Display omitted]